Yeast Bim1p Promotes the G1-specific Dynamics of Microtubules - Tirnauer, Jennifer S. (The Rockefeller University Press, 1999)
Microtubule dynamics vary during the cell cycle, and microtubules appear to be more dynamic in vivo than in vitro. Proteins that promote dynamic instability are therefore central to microtubule behavior in living cells. Here, we report that a yeast protein of the highly conserved EB1 family, Bim1p, promotes cytoplasmic microtubule dynamics specifically during G1. During G1, microtubules in cells lacking BIM1 showed reduced dynamicity due to a slower shrinkage rate, fewer rescues and catastrophes, and more time spent in an attenuated/paused state. Human EB1 was identified as an interacting partner for the adenomatous polyposis coli (APC) tumor suppressor protein. Like human EB1, Bim1p localizes to dots at the distal ends of cytoplasmic microtubules. This localization, together with data from electron microscopy and a synthetic interaction with the gene encoding the kinesin Kar3p, suggests that Bim1p acts at the microtubule plus end. Our in vivo data provide evidence of a cell cycle–specific microtubule-binding protein that promotes microtubule dynamicity.